THE RELATIONSHIP between COURSE MANAGEMENT and EXAMINATION ATTRITION RATES among UNDERGRADUATE MEDICAL STUDENTS at the UNIVERSITY OF ZAMBIA - Daka, Harrison; Banda, Sekelani S.; Namafe, Charles M. (International Journal of African Higher Education, 2020)
This study investigated the relationship between course management and examination attrition rates among undergraduate medical students at the University of Zambia, School of Medicine between the years 2008 to 2016. An explanatory sequential research design was used for data collection. Data were captured using an evaluation survey instrument, students’ Focus Group Discussion schedule and an interview schedule for key informants. Quantitative data from the first set were analysed using descriptive and inferential statistics while qualitative data from the second set were analysed using constant comparative method. The findings indicate that there was significant statistical difference in the course workloads in all programmes (p = 0.000, F = 4, 596, d f = 8.53). The course loads were heavy, had little time allocated to them. Course concepts were not taught in depth and led to students’ perceptions that the courses were difficult. As such, there is urgent need to revise or review course contents (i. e. curricular) of several programmes to be in accordance with the time allocated to them and that the Department of Medical Education and Development (DMED) should consider organizing specific pedagogical training programmes for existing and newly employed academic staff.